Modeling of galfenol bending actuator considering nonlinear hysteresis and dynamic real-time control strategy. (23rd February 2016) - Shu, Liang; Wu, Guichu; Chen, Dingfang; Dapino, Marcelo J
Abstract: On active bending structures, the actuation direction and the excitation field direction are not the same. Simple lumped parameter models are inadequate to describe the relationship between output displacement and input field. In this paper, a dynamic distributed parameter model is presented to describe the system dynamics of a galfenol bending actuator. To consider nonlinearities and hysteresis in bending, a nonlinear magnetomechanical model is developed to characterize the hysteretic magnetostriction generated by the galfenol layer. A dynamic real-time control strategy is proposed to compensate for hysteresis. A nonlinear inverse filter is constructed to linearize the hysteresis based on the proposed distributed parameter model. In order to increase the calculation efficiency, a new iteration method is proposed to calculate the filter. The iteration stepsize of the input field can be adaptively updated according to the inverting error. Simulation results show that significant enhancement of convergence efficiency can be achieved by using the proposed method compared with the existing fixed step size method. Experiments have been conducted to verify the real-time control strategy.